Droplet dynamics on slippery surfaces: small droplet, big impact. Issue 2 (24th June 2019) - Liu, Yahua; Yan, Xiantong; Wang, Zuankai
Abstract : The dynamic interaction of droplets with slippery surfaces is essential to various industrial applications, such as anti‐icing, water‐repellency or water‐harvesting, anti‐bacterial, and phase change heat transfer. With recent progress in materials, manufacturing as well as learning from nature, the physics of droplet dynamics has been greatly enriched owing to the emergence of peculiar wetting states manifested on bio‐inspired textured surfaces. This review is devoted to the discussion of the recent progress made in the authors' understanding of the dynamic interaction of small droplets with bio‐inspired surfaces. Particular attention is given to droplet impact on slippery surfaces, such as superhydrophobic surfaces characterised with air–solid–liquid triple‐phase interface and slippery lubricant infused porous surfaces characterised with the liquid/liquid two‐phase interface. Droplet spreading, retraction, contact time, elastodynamics as well as oblique impact are systematically reviewed. Finally, the authors offer their perspectives on this important and highly multidisciplinary research area.